Peran Good Corporate Governance Terhadap Kinerja Bank Perekonomian Rakyat - wulandari Wulandari; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2026)
This study looks at how Batam City's Rural Banks' (BPR) non-financial performance is affected by Good Corporate Governance (GCG). A Likert-scale questionnaire was used to gather quantitative data from 62 carefully chosen employees. Multiple linear regression was used for analysis, with validity, reliability, and classical assumption tests providing support. The findings show that transparency, accountability, and responsibility all significantly and favorably affect non-financial performance, especially when it comes to improving internal governance procedures, operational efficacy, and service quality. When combined, these GCG principles strengthen organizational discipline and promote more efficient decision-making within BPR operations. Overall, the findings indicate that strong GCG implementation not only improves institutional performance but also contributes to long-term sustainability, suggesting that BPR management should continually reinforce GCG practices to build stakeholder trust, increase operational efficiency, and enhance organizational competitiveness.